Drainage gas recovery technology for high-sulfur gas wells by a canned ESP system - Yang Peng; Changqing Ye; Fengjing Sun; Xueqiang Wang; Peng Zhu; Qing Zhu; Yu Zhang; Weilin Wang (Natural Gas Industry B, 2018)
In order to apply the electric submersible pump (ESP) based drainage gas recovery technology commonly used in conventional gas wells to high-sulfur gas wells, and meet the requirements of casing protection in high-sulfur gas wells, we conducted a series of technical researches on casing protection, gas interference and vibration of deep-well ESP set in terms of a completion string design and support tools based on the completion modes of high-sulfur gas wells and the technical characteristics of ESP drainage gas recovery technologies. Simultaneously, drainage gas recovery technology was designed for Well L2. The research and application results show: firstly, the completion string system of high-sulfur gas wells composed of a canned ESP system and an anchor intubation packer can realize the normal operation of ESP and meet the requirements of casing protection; secondly, multiphase pump and bleeder line can be used to solve the problem of gas interference, the automatic reverse valve can be used to reduce the effect of ESP complex flow path on the flowing of the gas well, and the anchor intubation packer can be used to reduce the string vibration; thirdly, the canned ESP system designed in this paper is applicable to Ø244.5 mm and Ø177.8 mm casings, specifically, the ESP corresponding to Ø244.5 mm casing has the maximum flow rate of 900 m3/d and the maximum lift height of 4500 m, and that corresponding to Ø177.8 mm casing has the maximum flow rate of 300 m3/d and the maximum lift height of 3000 m. It is concluded that this research result provides a technical support for the implementation of ESP based drainage gas recovery technology in high-sulfur gas wells. Keywords: High-sulfur gas well, Electric submersible pump, Drainage gas recovery, Canned system, Well completion method, Casing protection, Intubation packer, Multiphase pump